Full circle [videorecording (DVD)] - Palin, Michael; Palin, Michael; Mills, Roger; Mills, Roger; Vallance, Clem; Vallance, Clem (BBC Video ; Distributed in the USA and Canada by Warner Home Video, 2008)
Follows Michael Palin on a journey around the countries of the Pacific Rim. Begins in Alaska and travels to Kamchatka and the Pacific coast of Russia, Japan, South and North Korea, China, Vietnam, the Philippines, Malaysia, Indonesia, Australia, New Zealand, Chile, Bolivia, Peru, Colombia, Mexico, Los Angeles and San Francisco, California, and British Columbia, Canada.